Pemaknaan Kata Al-Kawakib Dalam Al-Qur’an Menurut Tafsir Al-Misbah - Listia Murni Hasibuan & Muhammad Arsad Nasution & Hasiah (IAIN Padangsidimpuan, 2021)
The Qur'an in Arabic has an interesting system of signs to study. Among the verses that are interesting to study are the verses about the stars. Which in the Qur'an the stars have different terms including, An-Najm, Al Masabih, Al-Tariq, Al-Kawakib, Al-Buruj and Al-Khunnas. Among these terms, the author is interested in raising the title of the word Al-Kawakib. Which Al-Kawakib in the Qur'an is interpreted as a star but in this case the author is interested in studying the meaning of Al-Kawakib in the Qur'an, then the problem formulation in this thesis is how the meaning of the word Al-Kawakib in Al- Qur'an according to Tafsir Al-Misbah. The type of research used in this thesis is library research, therefore the source of data is in the form of library materials that are primary and secondary. The word Al-Kawakib becomes a key word in the Qur'an in the Thematic tafsir, by collecting verses related to Al-Kawakib. The results of this study show that the word Al-Kawakib in the Qur'an there are five verses that mean Al-Kawakib as a Mediator to Know God Rationally, Al-Kawakib as a marker of the last days, Al-Kawakib as the Decorator ofhe Sky, Al-Kawakib As Parable Material. And Al-Kawakib As a description of the dream of Joseph saw 11 kaukab. Furthermore, Muhammad Quraish Shihab interpreted the verses about Al-Kawakib to be divided into two, namely the star in its apparent meaning and the star in its outward meaningless form, which is as contained in the QS. Yusuf [12]: 4, QS. An-Nur [24]: 35, that is, the star in the form of meaningless dzahirnya that is interpreted as power and guidance from God or guidance and in the QS. Al-An'Am [6]: 76, QS. As-Saffat [37]: 6 and QS.Al-Infitar [82]: 2, the star is meant as a star in its outward form that is in the form of its object.